2020
DOI: 10.1186/s12885-020-6596-y
|View full text |Cite
|
Sign up to set email alerts
|

Bone complications in patients with multiple myeloma in five European countries: a retrospective patient chart review

Abstract: Background: Bone complications (pathologic fracture, spinal cord compression, surgery to bone and radiation to bone) are a common problem in patients with multiple myeloma (MM). We set out to provide insights into the real-world burden of bone complications in patients with newly diagnosed MM (NDMM). Methods: We conducted a retrospective review of medical charts of patients with NDMM whose disease had progressed following first-line treatment in the 3 months before data collection in 2016 in five European coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 47 publications
0
12
0
3
Order By: Relevance
“…Zoledronic acid should be dose reduced already with a mild to moderate renal impairment (CrCl 30-60 mL/min) and is not recommended in patients with severe renal impairment (<30 mL/min). A recent publication, including patients from 5 European countries, showed that 51 % of all patients had renal insufficiency at the start of first line treatment, and 3% had severe renal impairment [89]. The study also found that a quarter of the patients with sufficient renal function never started bisphosphonate treatment.…”
Section: Bisphosphonatesmentioning
confidence: 89%
“…Zoledronic acid should be dose reduced already with a mild to moderate renal impairment (CrCl 30-60 mL/min) and is not recommended in patients with severe renal impairment (<30 mL/min). A recent publication, including patients from 5 European countries, showed that 51 % of all patients had renal insufficiency at the start of first line treatment, and 3% had severe renal impairment [89]. The study also found that a quarter of the patients with sufficient renal function never started bisphosphonate treatment.…”
Section: Bisphosphonatesmentioning
confidence: 89%
“…This prospective study is the first study in the literature which evaluated, in depth, the effects of Kd combination on bone health in patients with advanced RRMM in a real-world setting. Myeloma bone disease is a common feature for patients with MM; more than 70% present with osteolytic bone disease at diagnosis, whereas bone pain constitutes a very frequent presenting symptom leading to MM diagnosis [ 2 ]. In our study, 36% of the patients had a previous history of SREs at the time of Kd initiation.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with myeloma bone disease are at high risk of skeletal-related events (SREs) such as pathological fractures, compression of the spinal canal and need for surgery or radiotherapy due to bone-related complications. SREs add significantly to the disease burden by increasing morbidity, mortality and treatment costs [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Anemia (73%) is attributed to a reduction in erythropoietin production and suppressive effects of excess cytokines on erythropoiesis ( 19 ). Bone involvement (53%) manifests as either pain or pathological fractures due to bone infiltration by plasmacytoma, osteolytic bone lesions and osteoporosis ( 20 ).…”
Section: Delayed Diagnosis and Diagnostic Uncertaintymentioning
confidence: 99%